A network of empirical ethics teams embedded in research programmes across multiple sites: opportunities and challenges in contributing to COVID-19 research and responses - Ngwenya, N; Ilo Van Nuil, J; Nyirenda, D; Chambers, M; Cheah, PY; Seeley, J; Chi, P; Mafuleka, L; Nkosi, B; Kamuya, D; Davies, A; Schneiders, ML; et al. (F1000Research, 2023)
Covid-19 continues to teach the global community important lessons about preparedness for research and effective action to respond to emerging health threats. We share the COVID-19 experiences of a pre-existing cross-site ethics network-the Global Health Bioethics Network-which brings together researchers and practitioners from Africa, Europe, and Southeast Asia. We describe the network and its members and activities, and the work-related opportunities and challenges we faced over a one-year period during the pandemic. We highlight the value of having strong and long-term empirical ethics networks embedded across diverse research institutions to be able to: 1) identify and share relevant ethics challenges and research questions and ways of 'doing research'; 2) work with key stakeholders to identify appropriate ways to contribute to the emerging health issue response - e.g., through ethics oversight, community engagement, and advisory roles at different levels; and 3) learn from each other and from diverse contexts to advocate for positive change at multiple levels. It is our view that being embedded and long term offers opportunities in terms of deep institutional and contextual knowledge, existing relationships and access to a wide range of stakeholders. Being networked offers opportunities to draw upon a wide range of expertise and perspectives, and to bring together internal and external insights (i.e.drawing on different positionalities). Long term funding means that the people and resources are in place and ready to respond in a timely way. However, many tensions and challenges remain, including difficulties in negotiating power and politics in the roles that researchers and research institutions can and should play in an emergency, and the position of empirical ethics within research programmes. We discuss some of these tensions and challenges and consider the implications for our own and similar networks in future.